Security Analysis of HMAC/NMAC by Using Fault Injection - Kitae Jeong; Yuseop Lee; Jaechul Sung; Seokhie Hong (Journal of Applied Mathematics)
In Choukri and Tunstall (2005), the authors showed that if they decreased the number of rounds in AES by injecting faults, it is possible to recover the secret key. In this paper, we propose fault injection attacks on HMAC/NMAC by applying the main idea of their attack. These attacks are applicable to HMAC/NMAC based on the MD-family hash functions and can recover the secret key with the negligible computational complexity. Particularly, these results on HMAC/NMAC-SHA-2 are the first known key recovery attacks so far.